Guest‐Induced Transformation of a Porphyrin‐Edged FeII4L6 Capsule into a CuIFeII2L4 Fullerene Receptor1. Issue 13 (5th February 2015) - Wood, Daniel M.; Meng, Wenjing; Ronson, Tanya K.; Stefankiewicz, Artur R.; Sanders, Jeremy K. M.; Nitschke, Jonathan R.
Abstract The combination of a bent diamino(nickel(II) porphyrin) with 2‐formylpyridine and FeII yielded an FeII4L6 cage. Upon treatment with the fullerenes C60 or C70, this cage was found to transform into a new host–guest complex incorporating three FeII centers and four porphyrin ligands, in an arrangement that is hypothesized to maximize π interactions between the porphyrin units of the host and the fullerene guest bound within its central cavity. The new complex shows coordinative unsaturation at one of the FeII centers as the result of the incommensurate metal‐to‐ligand ratio, which enabled the preparation of a heterometallic cone‐shaped CuIFeII2L4 adduct of C60 or C70.